The mitigating effects of nitric oxide and hydrogen peroxide pre-treatments to salt-stressed strawberry plants - Christou, Anastasis; Papadopoulos, Ioannis; Fotopoulos, Vasileios; Manganaris, George A. (My University, 2011)
Nitric oxide (NO) and hydrogen peroxide (H202) are reactive nitrogen and oxygen species with a well-documented signaling role necessary for maintenance of cell redox homeostasis. In the present study we tested whether hydroponic pre-treatment of strawberry (Fragaria x ananassa cv. Camarosa) roots to H202 (10 mM for 8 h) and sodium nitroprusside (SNP - NO donor; 100 ~M for 48 h), could induce long lasting priming effects and tolerance to subsequent exposure to 100 mM NaCI for 8 d. Both root pre-treatments resulted in significantly reduced leaf chlorophyll degradation, ion leakage and lipid peroxidation levels in comparison with plants directly subjected to salt stress, suggesting a systemic mitigating effect of NO and H202 pre-treatments to cellular damage resulting from abiotic stress factors. Furthermore, both pre-treatments lead to reduced de novo synthesis of NO and H202 in leaves following salt stress, minimizing oxidative and nitrosative stress in strawberry plants. Finally, an NaCI stressinduced decrease in the ascorbate and glutathione redox state was partially prevented by both pre-treatments, providing strong evidence that H202 and NO elicit increased systemic antioxidant activity in strawberry plants under salt stress conditions.